2005
DOI: 10.1086/498689
|View full text |Cite
|
Sign up to set email alerts
|

RXTE Discovery of Multiple Cyclotron Lines during the 2004 December Outburst of V0332+53

Abstract: We present an analysis of the 2-150 keV spectrum of the transient X-ray pulsar V0332ϩ53 taken with the Rossi X-Ray Timing Explorer (RXTE) in 2004 December. We report on the detection of three cyclotron resonance features at 27, 51, and 74 keV in the phase-averaged data, corresponding to a polar magnetic field of 2.7 # G. After 4U 0115ϩ63, this makes V0332ϩ53 the second accreting neutron star in which more than two 12 10 cyclotron lines have been detected; this has now also been confirmed by INTEGRAL. Pulse-pha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
96
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(117 citation statements)
references
References 22 publications
18
96
3
Order By: Relevance
“…However, there is a qualitative agreement of the Suzaku data and the results by Fürst et al (2014) regarding the CRSF. Although observed in a number of other sources (e.g., 4U 0115+634 or V 0332+53, Heindl et al 1999;Pottschmidt et al 2005, respectively), we find no indications of a second harmonic, which we would expect around 24 keV, although PIN and NuSTAR are both very sensitive in this energy The best-fit parameters are given in Table 2, and Fig. 5 shows the phase-averaged spectrum and best-fit model of the second observation.…”
Section: Phase-averaged Spectroscopycontrasting
confidence: 48%
“…However, there is a qualitative agreement of the Suzaku data and the results by Fürst et al (2014) regarding the CRSF. Although observed in a number of other sources (e.g., 4U 0115+634 or V 0332+53, Heindl et al 1999;Pottschmidt et al 2005, respectively), we find no indications of a second harmonic, which we would expect around 24 keV, although PIN and NuSTAR are both very sensitive in this energy The best-fit parameters are given in Table 2, and Fig. 5 shows the phase-averaged spectrum and best-fit model of the second observation.…”
Section: Phase-averaged Spectroscopycontrasting
confidence: 48%
“…The next powerful outburst of V 0332+53 began at the end of 2004 ). An analysis of the follow-up observations performed with the RXTE and INTEGRAL observatories showed that beside the absorption feature at an energy of ∼ 26 keV, there are two additional similar features in the source spectrum at energies of ∼ 49 and ∼ 75 keV, which were interpreted as the second and third harmonics of the main cyclotron frequency Pottschmidt et al, 2005). A good coverage of the whole outburst (including rising and declining parts) with the RXTE observations allowed to Tsygankov et al (2006Tsygankov et al ( , 2010 to make a detailed spectral analysis and to show that the cyclotron line energy is not a constant but negatively correlated with the source luminosity and to obtain constraints on the magnetic field in the source as B NS ≃ 3.5 × 10 12 G. Moreover, the line energy as well as its width and depth are also strongly variable on the pulse period scale .…”
Section: Discussionmentioning
confidence: 99%
“…1 that the model adequately describes observations in a wide energy range 3-100 keV. Pottschmidt et al (2005) and Nakajima et al (2010) have discussed a complex structure of the V 0332+53 spectrum near the cyclotron line. This is also visible in the residuals of our spectra.…”
Section: Observations Spectral Model and Data Analysismentioning
confidence: 92%